# If in the expansion of ${\left( {1 + x} \right)^m}{\left( {1 - x} \right)^n}$ , the coefficients of $x$ and ${x^2}$ are 3 and -6 respectively, then the value of m is:

$A.$ 6

$B.$ 9

$C.$ 12

$D.$ 24

Last updated date: 18th Mar 2023

•

Total views: 308.7k

•

Views today: 6.87k

Answer

Verified

308.7k+ views

Hint: Use binomial theorem of series expansion.

Expanding both the terms of the above term we get:

\[

{\left( {1 + x} \right)^m}{\left( {1 - x} \right)^n} \\

= \left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right)\left( {1 - {}^n{C_1}{x^1} + {}^n{C_2}{x^2} - {}^n{C_3}{x^3} + ........} \right) \\

= 1\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\

- {}^n{C_1}{x^1}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\

+ {}^n{C_2}{x^2}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\

+ \cdots \cdots \cdots \\

\\

\]

Expanding the equation further to find the coefficients, we get:

\[ \Rightarrow 1 + x\left( {{}^m{C_1} - {}^n{C_1}} \right) + {x^2}\left( {{}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2}} \right) + \cdots \cdots \]

Hence, the coefficient of the term containing $x$ is

$

\Rightarrow {}^m{C_1} - {}^n{C_1} = 3 \\

\Rightarrow m - n = 3 \\

$ ---- (1)

Similarly coefficient of the term containing ${x^2}$ is

$

\Rightarrow {}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2} = - 6 \\

\Rightarrow m\left( {m - 1} \right) - 2mn + n\left( {n - 1} \right) = - 12 \\

\Rightarrow {m^2} - m - 2mn + {n^2} - n = - 12 \\

\Rightarrow {\left( {m - n} \right)^2} - \left( {m + n} \right) = - 12 \\

\Rightarrow 9 - \left( {m + n} \right) = - 12 \\

\Rightarrow m + n = 21 \\

$ ---- (2)

Adding equation 1 and 2 to find the value of m

$

\Rightarrow \left( {m + n} \right) + \left( {m - n} \right) = 21 + 3 \\

\Rightarrow 2m = 24 \\

\Rightarrow m = 12 \\

$

Hence option C is the correct answer.

Note: - In the above question binomial theorem of series expansion has been used in the very first step to expand the terms. We do not need to expand and multiply the whole series as we were concerned with only the first and second power of x so only two to three terms have been considered.

Expanding both the terms of the above term we get:

\[

{\left( {1 + x} \right)^m}{\left( {1 - x} \right)^n} \\

= \left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right)\left( {1 - {}^n{C_1}{x^1} + {}^n{C_2}{x^2} - {}^n{C_3}{x^3} + ........} \right) \\

= 1\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\

- {}^n{C_1}{x^1}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\

+ {}^n{C_2}{x^2}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\

+ \cdots \cdots \cdots \\

\\

\]

Expanding the equation further to find the coefficients, we get:

\[ \Rightarrow 1 + x\left( {{}^m{C_1} - {}^n{C_1}} \right) + {x^2}\left( {{}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2}} \right) + \cdots \cdots \]

Hence, the coefficient of the term containing $x$ is

$

\Rightarrow {}^m{C_1} - {}^n{C_1} = 3 \\

\Rightarrow m - n = 3 \\

$ ---- (1)

Similarly coefficient of the term containing ${x^2}$ is

$

\Rightarrow {}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2} = - 6 \\

\Rightarrow m\left( {m - 1} \right) - 2mn + n\left( {n - 1} \right) = - 12 \\

\Rightarrow {m^2} - m - 2mn + {n^2} - n = - 12 \\

\Rightarrow {\left( {m - n} \right)^2} - \left( {m + n} \right) = - 12 \\

\Rightarrow 9 - \left( {m + n} \right) = - 12 \\

\Rightarrow m + n = 21 \\

$ ---- (2)

Adding equation 1 and 2 to find the value of m

$

\Rightarrow \left( {m + n} \right) + \left( {m - n} \right) = 21 + 3 \\

\Rightarrow 2m = 24 \\

\Rightarrow m = 12 \\

$

Hence option C is the correct answer.

Note: - In the above question binomial theorem of series expansion has been used in the very first step to expand the terms. We do not need to expand and multiply the whole series as we were concerned with only the first and second power of x so only two to three terms have been considered.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Name the Largest and the Smallest Cell in the Human Body ?

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

A ball impinges directly on a similar ball at rest class 11 physics CBSE

Lysosomes are known as suicidal bags of cell why class 11 biology CBSE

Two balls are dropped from different heights at different class 11 physics CBSE

A 30 solution of H2O2 is marketed as 100 volume hydrogen class 11 chemistry JEE_Main

A sample of an ideal gas is expanded from 1dm3 to 3dm3 class 11 chemistry CBSE